The desgner’s perception and expert’s evaluation: testing techniques for problem exploration on a design methodology framework - VASCONCELOS, Luis Arthur de (Universidade Federal de Pernambuco, 2015)
Submitted by Amanda Silva (amanda.osilva2@ufpe.br) on 2015-03-09T14:33:30Z No. of bitstreams: 2 license_rdf: 1232 bytes, checksum: 66e71c371cc565284e70f40736c94386 (MD5) dissertacao_lalv.pdf: 3428243 bytes, checksum: 4cfc2cf496677e2d7b64975aee50848d (MD5) === Made available in DSpace on 2015-03-09T14:33:30Z (GMT). No. of bitstreams: 2 license_rdf: 1232 bytes, checksum: 66e71c371cc565284e70f40736c94386 (MD5) dissertacao_lalv.pdf: 3428243 bytes, checksum: 4cfc2cf496677e2d7b64975aee50848d (MD5) Previous issue date: 2012 === CAPES; CNPq === Understanding methodology in design as a schematized process composed by a set of steps in order to support problem solving, data mining or search for information activities are commonly performed on an initial step of this process, which can be called as problem exploration. This work focuses on identifying the influences that executing the problem exploration step can cause to the design team, as well to the final developed solutions. To achieve this objective, an initial investigation was performed in order to search for similar studies that could test these influences. After confirming the absence of such researches, an experiment was conducted to test techniques for problem exploration as a way to identify the possible influences of this step within the design process. The experiment was carried out in an undergraduate design class during four months and involved five groups of about six members each, who should develop concepts for problems about they did not have any previous information. Except for the problem exploration step, which could be performed differently, the five groups executed an identical framework of methods for problem solving. All documentation produced by the design teams was evaluated for a selected group of experts. As results for the experiment, it was concluded that the use of such problem exploration techniques gave more confidence to designers when responding to how well informed they were about the problem after confronting it, and although different groups performed distinct procedures as regards the tested step, no difference on the experts’ evaluation for the alternatives could be perceived. This way utilizing problem exploration techniques caused no influences on the final solutions developed.